THE INFLUENCE OF YLANG-YLANG ESSENTIAL OIL (cananga odorata) AND VIRGIN COCONUT OIL (VCO) ON THE CHARACTERISTICS OF HAND & BODY LOTION - Febrina, Sarah (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACT This study aims to explore the influence of ylang-ylang essential oil (Cananga odorata) and virgin coconut oil (VCO) on antioxidant, antibacterial, and organoleptic properties in the production of hand body lotion. Ylang ylang oil is known for its various health benefits, including antioxidant and antibacterial properties, while VCO is increasingly popular as a functional food oil with anti-inflammatory and antimicrobial properties. The methods used include distillation to produce essential oil, followed by physical characteristic analysis and effectiveness testing. Lotion formulation was conducted with varying proportions of essential oil and VCO. Tests conducted include antioxidant testing using the DPPH method, bacterial testing to determine antibacterial effectiveness, and organoleptic testing to evaluate the fragrance and moisturizing properties of the lotion. The research results showed that lotion formulations with specific proportions of ylang-ylang essential oil and VCO produced significant antioxidant activity, with IC50 values indicating strong antioxidant potential. In addition, bacterial tests showed that the lotion was effective in reducing bacterial colony counts, meeting microbial contamination standards according to SNI. Organoleptic test results showed a positive preference from panelists for the fragrance and moisturizing properties of the lotion, with some samples receiving excellent ratings.Key words: Essential Oil, Ylang-Ylang Flower, Virgin Coconut Oil (VCO), Hand Body Lotion, Antioxidant, Antibacterial, and Organoleptic Testing.